2019
DOI: 10.1002/ange.201912195
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Vapor‐Induced Reversible Single‐Crystal‐to‐Single‐Crystal Transformation of a Triphosphaazatriangulene‐Based Metal–Organic Framework

Abstract: At riphosphaazatriangulene (H 3 L) was synthesized through an intramolecular triple phospha-Friedel-Crafts reaction. The H 3 Lt riangulene contains three phosphinate groups and an extended p-conjugated framework, which enables the stimuli-responsive reversible transformation of [Cu(HL)-(DMSO)•(MeOH)] n ,a3D-MOF that exhibits reversible sorption characteristics,i nto (H 3 L•0.5 [Cu 2 (OH) 4 •6 H 2 O] •4 H 2 O), a1 D-columnar assembled proton-conducting material. The hydrophilic nature of the latter resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The single crystal to single crystal (SCSC) transformation might occur when the crystal is subjected to different external influences such as heat, [23] solvent and pH in different external environments [24] and gives it new properties. However, studies on the effect of SCSC transformation on proton conductivity are rarely reported [25] . Chen [14] et al .…”
Section: Introductionmentioning
confidence: 99%
“…The single crystal to single crystal (SCSC) transformation might occur when the crystal is subjected to different external influences such as heat, [23] solvent and pH in different external environments [24] and gives it new properties. However, studies on the effect of SCSC transformation on proton conductivity are rarely reported [25] . Chen [14] et al .…”
Section: Introductionmentioning
confidence: 99%